Pentalogy of Cantrell. A stillbirth case report - Maribel Palencia Palacios; Blanca Viviana Fajardo Idrobo; Valentina López Mosquera; Jaime Antonio Álvarez Soler (Case Reports)
Introduction: Pentalogy of Cantrell is a rare congenital disorder characterized by midline birth anomalies. Its embryological origins are related to anomalies of the abdominal wall that prevent the closure of the thorax. Its etiology is not yet clear, but it has been associated with a failure of migration of the lateral plate mesoderm to the midline.